The Impact of Human Capital on Competitive Performance: An Empirical Study on Jordanian Pharmaceutical Companies - ALmasarweh, Mohammad Salameh Yousef (European Scientific Journal, ESJ, 2016)
The study is aimed at knowing the impact of human capital on competitive performance in Jordanian pharmaceutical companies. The study sample consisted of Jordanian human medicines manufacturing companies listed in the Jordanian Association of Pharmaceutical Manufacturers’ records of manufacturing companies for 2015. This amounted to 15 companies. The sampling unit and the analysis included individuals working in these companies from managers to department heads at various administrative levels. To achieve its objectives, the study used descriptive analytical method. This method was applied to collect and analyze data and test hypotheses through a questionnaire, which was used as a tool for the collection of information in the field of study. The study found a number of results, most important of which is: the existence of a statistically significant relationship between human capital (learning; knowledge; and skills) and competitive performance in Jordanian pharmaceutical companies at a level of significance of 0.05. The study recommended that attention be given to human capital in the companies, which will lead to an improvement in the level of the company, as well as an expansion of its market share and maximizing of its strengths.